The elasticity of natural hypersthene and the effect of Fe and Al substitution. Issue 1 (2nd January 2016) - Xu, Zhishuang; Ma, Maining; Li, Baosheng; Hong, Xinguo; Han, Lin; Zhou, Xiaoya
ABSTRACT: Compressional behavior of a natural hypersthene has been investigated at pressures up to 10.1 GPa at room temperature using in situ synchrotron X-ray diffraction in a diamond anvil cell. No phase transition was observed within the experimental pressure range. The pressure–volume data have been fitted with a third-order Birch–Murnaghan equation of state, resulting in K 0  = 113.6(6.2) GPa and K 0 ′ = 7.7 ( 2.0 ) for the bulk modulus and its pressure derivative with a fixed unit-cell volume V 0  = 854.0(6) Å 3 . The unit-cell parameters, a, b, and c, decrease nonlinearly with elevated pressure and show an anisotropic axial compressibility with a ratio βa : βb : βc : =1:2.05:1.3. The comparison with previous results of orthopyroxene reveals that Al substitution causes a decrease in unit-cell volume and an increase in the bulk modulus, whereas the incorporation of Fe has opposite effects. The relation between unit-cell volume and En/Ts contents has been obtained, V 0 (Å 3 ) = 873.7(1.1) − 40.8(1.44)  ×  En-90.6(14.7)  ×  Ts, which permits the prediction of unit-cell volume for Fe- and Al-bearing orthopyroxene system.